The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jat.4071
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and neonatal subchronic toxicity assessment of a novel mixture of the human‐identical milk oligosaccharides lacto‐N‐fucopentaose I and 2′‐fucosyllactose

Abstract: Human milk oligosaccharides (HMOs) are a complex group of bioactive molecules largely observed in human breast milk but also occurring in limited amounts in other mammalian milks. Advances in biotechnology have enabled production of humanidentical milk oligosaccharides (HiMOs), structurally identical molecules to HMOs found naturally in human milk, intended for addition to infant formula to more closely replicate breast milk. Biosynthesis of a novel mixture of two major HMOs, lacto-N-fucopentaose I and 2 0-fuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Differences in triiodothyronine (T3) concentrations were reported in a recent 90‐day neonatal study testing a novel mixture of lacto‐ N ‐fucopentaose I (LNFP‐I) and 2′‐FL (Phipps et al, 2021), the first published HiMO 90‐day study following the requirements of the most recent OECD Test Guideline 408, which was revised in 2018 to include additional endocrine‐related parameters such as thyroid hormones, low‐density lipoprotein‐cholesterol and high‐density lipoprotein‐cholesterol, and collection of vaginal smears for estrous cycle measurement (OECD, 2018). However, there were no differences in T3 or any other thyroid hormone concentrations between controls and 3‐FL groups in this study, which reinforces that the T3 differences reported for the LNFP‐I and 2′‐FL mixture were likely to have been biologically irrelevant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Differences in triiodothyronine (T3) concentrations were reported in a recent 90‐day neonatal study testing a novel mixture of lacto‐ N ‐fucopentaose I (LNFP‐I) and 2′‐FL (Phipps et al, 2021), the first published HiMO 90‐day study following the requirements of the most recent OECD Test Guideline 408, which was revised in 2018 to include additional endocrine‐related parameters such as thyroid hormones, low‐density lipoprotein‐cholesterol and high‐density lipoprotein‐cholesterol, and collection of vaginal smears for estrous cycle measurement (OECD, 2018). However, there were no differences in T3 or any other thyroid hormone concentrations between controls and 3‐FL groups in this study, which reinforces that the T3 differences reported for the LNFP‐I and 2′‐FL mixture were likely to have been biologically irrelevant.…”
Section: Discussionmentioning
confidence: 97%
“…Both tests were conducted in triplicate. Preparation of cell cultures, incubation conditions, colony counting, and evaluation of the assay results were performed as previously described by Phipps et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…The studies which were claimed proprietary by the applicant are listed in Table 11. Experimental designs with main results are included in a relevant publication (Phipps et al., 2020).…”
Section: Assessmentmentioning
confidence: 99%
“…In the in vitro mammalian cell micronucleus test in human lymphocytes (Phipps et al., 2020; Study Report, 2020b), concentrations of 555, 1110 and 2220 μg NF/mL (corresponding to up to 2000 μg/mL of LNFP‐I/2’‐FL mixture) were tested in the main study in the presence (3‐hour treatment) and absence (3‐ and 20‐hour treatments) of S9 metabolic activation. No cytotoxicity or precipitation were observed and the percentage of micronuclei in cultured human lymphocytes was not significantly increased in any of the test substance concentrations.…”
Section: Assessmentmentioning
confidence: 99%
“…There is therefore an urgent need for its large-scale production. Extraction of LNFP-I from cow’s milk is not feasible due to its low concentration and extremely high cost ( Bode et al, 2016 , Phipps et al, 2021 ). Enzymatic synthesis of LNFP-I has been achieved using bacterial α 2FTs.…”
Section: Introductionmentioning
confidence: 99%